First-principles investigation of the bulk and low-index surfaces of MoSe2 - Mirhosseini, Hossein; Roma, Guido; Kiss, Janos; Felser, Claudia (Physical Review B - Condensed Matter and Materials Physics, 2014)
In the framework of density functional theory, the geometry, electronic structure, and magnetic properties of the bulk and low index surfaces of MoSe2 have been studied. We have carried out calculations with various exchange-correlation functionals to select one which is able to describe the van der Waals (vdW) interactions and gives the best geometry compared with experiments. The inclusion of the vdW forces, however, does not guarantee a reliable description for the geometry of this compound: some vdW functionals strongly overestimate the interlayer distance, similar to GGA functionals. Our investigation shows that the recently introduced optB86b-vdW functional yields the best results for MoSe2. The vdW functionals have less impact on the electronic structure: the differences between the band structures of the experimental atomic structure, calculated by the vdW-DF and PBE functionals are marginal. We have tried the HSE06 hybrid functional as well but the results are not satisfactory: the overestimated interlayer distance leads to a significant overestimation of the band gap. The band structure of the bulk and monolayer is calculated and by the analysis of the bands character the indirect to direct band-gap transition is explained. The surface energy, work function and band structure of the surfaces are calculated as well. The role of the MoSe2 buffer layer in Cu(In,Ga)Se2 based solar cells is discussed by considering the work function values. © 2014 American Physical Society.
CRIS-Team Scopus Importer:2023-03-20